Hydro-Oceanographic Features of North Maluku Archipelagic Waters in January and July 2021 - Angkotasan, Abdul Motalib; Tawari, Ruslan H.S.; Bemba, Jefri; Natih, Nyoman M.N.; Suhaemi, Suhaemi (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
The waters of North Maluku are located in the Southern Pacific Ocean and are the eastern route of the Indonesian Throughflow, which contributes to the hydro-oceanographic conditions. The research aims to examine the hydro-oceanographic conditions of the island waters around North Maluku. Data obtained from measurement results and data reanalysis (www.marinecopernicus.eu) for the period December 2020–August 2021. Data analysis using Ocean Data View and Ferret software. The results of the analysis show that the west monsoon wind from the northwest blows at a speed of 2 m/s. The current movement pattern moves to the southeast. In the east season, the dominant wind blows from the southeast and south. Spasial temperatures in the two seasons are different between the waters of Termadoreh and Buli Bay. In January, the sea surface temperature in Termadoreh and Buli Bay averaged 29 °C and 30.50 °C. Meanwhile, in July, the average was between 29.50 and 29.70 °C. For salinity characteristics, in January, the Halmahera Sea was higher (34.2–34.8 psu) than the Maluku Sea (33.6-34.0 psu)